2021
DOI: 10.3390/s21134577
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Autoregressive Model for Estimation of Visitors’ Dynamic Agglomeration Patterns Near Event Location

Abstract: The rapid development of ubiquitous mobile computing has enabled the collection of new types of massive traffic data to understand collective movement patterns in social spaces. Contributing to the understanding of crowd formation and dispersal in populated areas, we developed a model of visitors’ dynamic agglomeration patterns at a particular event using dynamic population data. This information, a type of big data, comprised aggregate Global Positioning System (GPS) location data automatically collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…There is an interactive phenomenon between environmental regulation and GWRE, and a certain agglomeration pattern has gradually formed in space [49]. In fact, the coupling and coordination between environmental regulation and GWRE not only reflects the differences in space and driving mechanisms, but also shows a certain degree of spatial regularity.…”
Section: Coupling and Coordination Analysis Between Environmental Reg...mentioning
confidence: 99%
“…There is an interactive phenomenon between environmental regulation and GWRE, and a certain agglomeration pattern has gradually formed in space [49]. In fact, the coupling and coordination between environmental regulation and GWRE not only reflects the differences in space and driving mechanisms, but also shows a certain degree of spatial regularity.…”
Section: Coupling and Coordination Analysis Between Environmental Reg...mentioning
confidence: 99%
“…Dong et al 22 conducted a recovery analysis of Beijing at a spatial scale of 1.0 km × 1.0 km. Related to Nagoya, socioeconomic factors and land use patterns at the zip-code level are revealed to influence the frequency of visiting green infrastructures during the COVID-19 34 ; using mobile spatial statistics (with a minimal mesh of 1.0 km × 1.0 km) to evaluate the characteristics of population at different stages of COVID-19, it is found that population recovery is more robust at Nagoya Station and Sakae on weekdays and holidays 35 (note that in Nagoya, its central area was the most visited place before the pandemic 36 , 37 , similar to other cities in Japan; but no study had not been done on the influences of pre-pandemic social-economic activity patterns on urban recovery). Similar cross-space associations may exist in the urban recovery that needs to be realized over wider areas; however, little has been done from such a perspective.…”
Section: Introductionmentioning
confidence: 99%